Revision of Trichiscus Benoît, 1956 (Hymenoptera, Bethylidae) - Azevedo, Celso O. (Zootaxa, 2014)
The species of the Afrotropical genus Trichiscus are revised. Fourteen species are recognized, two previously described species, T. wittei Benoît and T. suzannae Benoît, and twelve new: T. noorti sp. nov., T. denisi sp. nov., T. briani sp. nov., T. copelandi sp. nov., T. mourei sp. nov., T. lynnae sp. nov., T. normani sp. nov., T. luboi sp. nov., T. zuparkoi sp. nov., T. ohli sp. nov., T. camargoi sp. nov. and T. jimi sp. nov.. A key to species is proposed.